Analisis IImplementasi Kompetensi Kepribadian Guru Dalam Motivasi Belajar di MTSS Muhammadiyah-15 Medan - Laila Wardati (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
Education has a very important role in shaping the personality and the development of human civilization. Teacher’s Personality is an abstract problem that can only be seen through appearance, action, speech, manner of dress and in the face of every teacher has a problem thet every private individual in accordance with the characteristics of personality he ha. personality is something yhat is very determine the level of authority of a teacher in the eyes of students and society. This study aims to Determine Analysis of the implementation of the Personal Competence of teachers in learning motivation in MTs Muham-madiyah 15 Medan. The Qualitative Research method is Descriptive, Which becomes its own instrument or tool of researchers, data obtained from two sources, namely primary sources and secondary sourcer with techniques of data collection through observation, interview and documentation. The technique of data analysis is done inductively. The results showed that Analysis of the implementation of the Personal Competence of teachers in learning motivation in MTs Muhammadiyah 15 Medan properly. With the indicator: a). teachers have a stable life, b). teachers have a mature attitude, c). authoritative teacher, d). the teacher has a finer quality and can be used as an example.